Blood Pressure and Outcome After Mechanical Thrombectomy With Successful Revascularization: A Multicenter Study. Issue 9 (September 2019) - Anadani, Mohammad; Orabi, Mohamad Y.; Alawieh, Ali; Goyal, Nitin; Alexandrov, Andrei V.; Petersen, Nils; Kodali, Sreeja; Maier, Ilko L.; Psychogios, Marios-Nikos; Swisher, Christa B.; Inamullah, Ovais; Kansagra, Akash P.; et al.
Abstract : Background and Purpose—: Successful reperfusion can be achieved in more than two-thirds of patients treated with mechanical thrombectomy. Therefore, it is important to understand the effect of blood pressure (BP) on clinical outcomes after successful reperfusion. In this study, we investigated the relationship between BP on admission and during the first 24 hours after successful reperfusion with clinical outcomes. Methods—: This was a multicenter study from 10 comprehensive stroke centers. To ensure homogeneity of the studied cohort, we included only patients with anterior circulation who achieved successful recanalization at the end of procedure. Clinical outcomes included 90-day modified Rankin Scale, symptomatic intracerebral hemorrhage (sICH), mortality, and hemicraniectomy. Results—: A total of 1245 patients were included in the study. Mean age was 69±14 years, and 51% of patients were female. Forty-nine percent of patients had good functional outcome at 90-days, and 4.7% suffered sICH. Admission systolic BP (SBP), mean SBP, maximum SBP, SBP SD, and SBP range were associated with higher risk of sICH. In addition, patients in the higher mean SBP groups had higher rates of sICH. Similar results were found for hemicraniectomy. With respect to functional outcome, mean SBP, maximum SBP, and SBP range were inversely associated with the good outcome (modified Rankin Scale score, 0–2). However, the difference in SBP parameters between the poor and good outcome groups was modest. Conclusions—: Higher BP within the first 24 hours after successful mechanical thrombectomy was associated with a higher likelihood of sICH, mortality, and requiring hemicraniectomy. Abstract : Supplemental Digital Content is available in the text.